The Political Personal Realm in the Draft Law on the Elimination of Sexual Violence in Indonesia - Tambunsaribu, Risna Desimory; Widiantini, Ikhaputri (Yayasan Jurnal Perempuan, 2021)
This article is using a critical interpretation based on radical feminist theory to analyze the issue of sexual violence against women in Indonesia. Based on data from Komnas Perempuan in 2020, the number of victims of sexual violence is increasing. The root of sexual violence comes from the biological differences between women and men that has been constructed in society. Men are considered to have sexual dominance on women. The existence of sexual politics maintains by the state have taken away women’s authority both in private and public spheres. Using the critical and praxis feminist approach, this article assesses the data research from Komnas Perempuan, especially related to cases of sexual violence. The analysis and criticism of sexual politics in this article also highlights the Draft Law on the Elimination of Sexual Violence. The analysis proves the importance of state involvement in ensuring the lives of Indonesian female citizens, especially concerning protection from sexual violence.